PERAN PELAKU UMKM DALAM MEMANFAATKAN DIGITAL MARKETING DALAM MENINGKATKAN KETAHANAN EKONOMI DI DESA MONTOR KAB. PANDEGLANG BANTEN - Wisnubroto, Agung Prabowo; Saputra, Saripudin; Mahendra, Yoga; Ramadhanti, Anita; Septia, Nabila Amelinda; Sopiyanti, Opi (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in Montor Village, Pandeglang Regency, Banten, in utilizing digital marketing to strengthen the village’s economic resilience. The research background is based on local economic challenges caused by limited market access, low digital literacy, and the impacts of the pandemic that have hindered conventional sales activities. This research employed a qualitative descriptive approach with data collected through in-depth interviews, participatory observation, and documentation involving 15 MSME actors. Data analysis was conducted through data reduction, presentation, and conclusion drawing, with source triangulation to enhance validity. The results indicate that the utilization of digital marketing—particularly through social media platforms such as Facebook, Instagram, and WhatsApp Business—significantly contributes to expanding market reach, increasing sales volume, and strengthening the competitiveness of local products. MSME actors who actively adopt creative content strategies, paid promotions, and collaborations with local influencers have experienced a sales turnover increase of up to 35% in the last six months. Furthermore, digital marketing has contributed to the village’s economic resilience by creating new job opportunities, improving local economic circulation, and enhancing the branding of village products. In conclusion, digital marketing serves not only as a promotional tool but also as a strategic instrument for fostering village economic independence. Therefore, policy support is needed in the form of digital literacy training, adequate internet infrastructure, and continuous mentoring for MSME actors to ensure the optimal implementation of digital transformation.